Sustainable Cannabis Nutrition: Elevated root-zone phosphorus significantly increases leachate P and does not improve yield or quality - Westmoreland, F. Mitchell; Bugbee, Bruce (Frontiers in Plant Science, 2022)
Phosphorus (P) is an essential but often over-applied nutrient in agricultural systems. Because of its detrimental environmental effects, P fertilization is well studied in crop production. Controlled environment agriculture allows for precise control of root-zone P and has the potential to improve sustainability over field agriculture. Medical Cannabis is uniquely cultivated for the unfertilized female inflorescence and mineral nutrition can affect the yield and chemical composition of these flowers. P typically accumulates in seeds, but its partitioning in unfertilized Cannabis flowers is not well studied. Here we report the effect of increasing P (25, 50, and 75 mg P per L) in continuous liquid fertilizer on flower yield, cannabinoid concentration, leachate P, nutrient partitioning, and phosphorus use efficiency (PUE) of a high-CBD Cannabis variety. There was no significant effect of P concentration on flower yield or cannabinoid concentration, but there were significant differences in leachate P, nutrient partitioning, and PUE. Leachate P increased 12-fold in response to the 3-fold increase in P input. The P concentration in the unfertilized flowers increased to more than 1%, but this did not increase yield or quality. The fraction of P in the flowers increased from 25 to 65% and PUE increased from 31 to 80% as the as the P input decreased from 75 to 25 mg per L. Avoiding excessive P fertilization can decrease the environmental impact of Cannabis cultivation.